2017
DOI: 10.7717/peerj.3173
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of fibroblast growth factor receptor 1 expression in neurons and glia

Abstract: BackgroundFibroblast growth factors (FGFs) and their receptors (FGFRs) have numerous functions in the developing and adult central nervous system (CNS). For example, the FGFR1 receptor is important for proliferation and fate specification of radial glial cells in the cortex and hippocampus, oligodendrocyte proliferation and regeneration, midline glia morphology and soma translocation, Bergmann glia morphology, and cerebellar morphogenesis. In addition, FGFR1 signaling in astrocytes is required for postnatal ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Still related to their transporter properties, GLUT1–known as facilitated glucose transporter member 1 ( Slc2a1 )–is expressed in β 1 tanycytes and, to a lesser extent, in β 2 tanycytes (3436). β tanycytes have also restricted expression of neural stem markers such as Sox2 (16, 17, 37, 38) , Fgf-10 (17, 39, 40), Blbp (17), and Musashi1 (17), as well as several growth factor receptor genes, such as Fgfr1 (38, 41) and Cntfr (42), consistent with their stem/ progenitor cell function. In contrast, the gene markers of α tanycytes are more similar to non-tanycyte ependymal cells than β tanycytes.…”
Section: Molecular Insights Into Tanycyte Classification and Metabolimentioning
confidence: 90%
“…Still related to their transporter properties, GLUT1–known as facilitated glucose transporter member 1 ( Slc2a1 )–is expressed in β 1 tanycytes and, to a lesser extent, in β 2 tanycytes (3436). β tanycytes have also restricted expression of neural stem markers such as Sox2 (16, 17, 37, 38) , Fgf-10 (17, 39, 40), Blbp (17), and Musashi1 (17), as well as several growth factor receptor genes, such as Fgfr1 (38, 41) and Cntfr (42), consistent with their stem/ progenitor cell function. In contrast, the gene markers of α tanycytes are more similar to non-tanycyte ependymal cells than β tanycytes.…”
Section: Molecular Insights Into Tanycyte Classification and Metabolimentioning
confidence: 90%
“…For example, FGF2 binds with a high affinity to FGFR1, while FGF18 preferentially binds to FGFR3 26,61 . In contrast to FGFR3, signaling through FGFR1 induces proliferation in both embryonic and human adult stem cells and is important for neurogenesis and proliferation and fate specification of radial glial cells in the cortex and hippocampus 6265 . Our data also demonstrated that FGF2 treatment induced higher proliferation of astrocytes compared to FGF18 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While FGFR1 is widely found in the hippocampus and in various parts of the cortex, FGFR2 and FGFR3 proteins are scattered throughout the CNS, and their expression profile changes with the brain development. FGFR4 is less abundant than other FGFRs and is mainly localized to the medial habenular nucleus [44,45,46,47,48]. The FGFRs are involved in the development, function and maintenance of the CNS [49].…”
Section: Cross-talk Between Fgfrs and G-protein-coupled Receptors mentioning
confidence: 99%